2018
DOI: 10.1002/jbm.a.36469
|View full text |Cite
|
Sign up to set email alerts
|

Composite tendon implant based on nanofibrillar polyhydroxybutyrate and polyamide filaments

Abstract: The composite material based on reinforcement of polyamide filaments enclosed by a nonwoven matrix of nanoscaled bioresorbable poly(3-hydroxybutyrate) fibers was developed for application as an artificial ligament implant. The aim of this study was to investigate biodegradability and biocompatibility of the developed implant, as well as its stress-strain properties. The study results show the polyamide core of the implant has stress-strain properties comparable with a natural ligament. Simultaneously, the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Equation (5) reflects the relation between the kinetic and diffusion constants, and thus provides another way to evidence that the CHD transport in the system is complicated by the degradation process. As was shown previously in [15,17,65], films, microspheres, ultrathin fibrils of PHB, and its blends with PLA or chitosan slowly degrade in aqueous media in accordance with a zero-order equation. Moreover, recent studies of degradation in a hydrolytic medium or in the presence of enzymes showed that the surface of the biopolymer is involved in the loss of weight of PHB (S-type degradation) [57].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Equation (5) reflects the relation between the kinetic and diffusion constants, and thus provides another way to evidence that the CHD transport in the system is complicated by the degradation process. As was shown previously in [15,17,65], films, microspheres, ultrathin fibrils of PHB, and its blends with PLA or chitosan slowly degrade in aqueous media in accordance with a zero-order equation. Moreover, recent studies of degradation in a hydrolytic medium or in the presence of enzymes showed that the surface of the biopolymer is involved in the loss of weight of PHB (S-type degradation) [57].…”
Section: Resultssupporting
confidence: 70%
“…Biocompatibility observed at therapeutic and clinical levels allows PHB to be applied as prosthesis, heart valves and stents, bone drug release systems, surgical threads, fibrillar implants, scaffolds in tissue engineering, and other uses [14,15,16,17,18]. Importantly, all the representatives of PHAs, including PHB, are biocompatible with cells and tissues, and hence PHB-based food packaging can be in long-term contact with meat, fish and other food components without tangible damage.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy is to create multiscale nanofibrous textile-based scaffolds using strands or yarns of nanofibers ( Almeida et al, 2019 ; Chen et al, 2021d ; Ma et al, 2022 ). Another method is to coat the fabric with nanofibers ( Chen L. et al, 2020 ; Olkhov et al, 2018 ). Nanofibrous strands or yarns have the potential to reconstruct the structure of natural collagen fibers ( Figure1 ) in tendon nanofibrous to microfibrous construction ( Mouthuy et al, 2015 ; Cai et al, 2020 ).…”
Section: Nanofiber-based Scaffoldsmentioning
confidence: 99%
“…They are constantly in high demand and scientist are seeking additional polymeric carriers for this application [2]. Researchers have documented the attractive clinical application, biocompatibility and potent drug release modulating properties of different aliphatic polyamides [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Yet, there is still not much information regarding their use as extended release drug carriers.…”
Section: Introductionmentioning
confidence: 99%